2018
DOI: 10.1002/jcp.26325
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA MALAT1 contributes to non‐small cell lung cancer development via modulating miR‐124/STAT3 axis

Abstract: lncRNAs can exert many biological effects in several cancer types. MALAT1 is a kind of lncRNA which is greatly overexpressed in several tumors including non-small cell lung cancer (NSCLC). However, the mechanism of MALAT1 in NSCLC still remains unclear. In our current study, we concentrated on the biological mechanism of MALAT1 in NSCLC. It was observed that MALAT1 was significantly upregulated in five human NSCLC cells including A549, H23, H522, H1299, and H460 cells compared to normal bronchial epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 42 publications
7
95
0
Order By: Relevance
“…For example, lncRNA MALAT1 is significantly up-regulated in 5 kinds of human NSCLC cells. Bioinformatic analysis has predicted a correlation between miR-124 and MALAT1 and indicated that STAT3 is the new mRNA target of miR-124 [24]. In this study, the results of bioinformatic tools on line and luciferase experiments showed that miR-661 targeted the 3'-UTR of lncRNA GAPLINC, and GAPLINC served as a molecular sponge for miR-661.…”
Section: Discussionmentioning
confidence: 82%
“…For example, lncRNA MALAT1 is significantly up-regulated in 5 kinds of human NSCLC cells. Bioinformatic analysis has predicted a correlation between miR-124 and MALAT1 and indicated that STAT3 is the new mRNA target of miR-124 [24]. In this study, the results of bioinformatic tools on line and luciferase experiments showed that miR-661 targeted the 3'-UTR of lncRNA GAPLINC, and GAPLINC served as a molecular sponge for miR-661.…”
Section: Discussionmentioning
confidence: 82%
“…7,8 Convincing evidence has demonstrated that a large amount of lncRNAs are frequently dysregulated in human cancers and contribute to tumor development and progression. 9 Currently, multiple lncRNAs, such as lncRNA HNF1A-AS1, 10 MIAT, 11 and MALAT1, 12 have been identied to be involved in NSCLC progression. Human urothelial carcinoma associated 1 (UCA1), located at chromosome 19p13.12 with 1.4 kb in length, is a wellcharacterized lncRNA that was initially identied in human bladder carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between Lnc-RNAs and STAT3 signaling has been described in multiple tumor cells [18–20]. In this study, we elucidated the role of Lnc-DC in dendritic cells mediated by TLR9/STAT3 signaling.…”
Section: Discussionmentioning
confidence: 79%